An Anthropological Approach to Discourse of Natural Heritage and Rural Tourism - Alizadeh, Fereshteh; Ahmadi, Fatemeh (International Journal of Engineering and Technology, 2018)
As a cultural subject, rural tourism is a novel concept which is the result of a dialogue between modernism and today’s newfangled world; but the study of nature’s social life and the relationship between human and nature is very old and its origins are far older than the knowledge of ethnography in a way that during centuries, different fields such as anthropogeography, cultural ecology and ethno-biology has been originated from this relationship. If we accept that one of the main incentives of rural tourists is the pleasure of seeing landscapes and natural heritage, studying the theoretical dimensions of the natural heritage can help the tourism policy makers to plan. As mentioned before, rural tourism is still young and its theoretical dimensions has not been studied very much.